La responsabilità sociale d'Impresa - prospettive teoriche nel dibattito italiano - Pier Luigi Sacco; Michele Viviani (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2006)
– This paper is meant as a discussion of different methodological approaches to the analysis of corporate social responsibility (CSR), sorted out through a scrutiny of the literature that has emerged from the recent Italian debate. The first stream of literature is embedded in the neo-classical approach that adapts – to the contemporary economic environment - the famous Milton Friedman's statement that the social responsibility of the firm is to make profits (Friedman, 1970). The second stream refers to a neo-contractualist approach, mainly developed by Lorenzo Sacconi (2004, 2005), that can be considered as an insightful application of incomplete contracts theory, strongly characterized by a contractualist-oriented ethical perspective. The third stream is the relational approach developed by Bruni and Zamagni (2004), which takes the issue of social reproduction into account in the description of the economic system, thereby looking at firms as producers of socially provided goods. Finally, we propose an integration between these different perspectives through the adoption of a conventionalist definition of CSR.
Keywords: 330